REVITALISASI PERAN PEMBELAJARAN IPS DALAM PEMBENTUKAN KARAKTER BANGSA - Sardiman, Sardiman (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Revitalization of Roles of the Learning of Social Studies in the Nation’s Character Building. Revitalization of roles of the learning of social studies needs to be made as soon as possible, because so far the learning implementation is not relevant to its objective and purpose. The learning of social studies has an important role in character education. Therefore, it is necessary to make improvement and upgrade steps. The curriculum design and competence standard of graduates should be based on student reality and humanity values, and should emphasize not only on materials mastery. The approach of essentialism has to be changed into the social reconstruction theory. The learning process is developed as a cultural transaction process which becomes an inseparable part of student character development. The learning model emphasizes more on active and participative learning. Besides, in order to strenghten roles of the learning of social studies in developing character education, a good environment condition, including the political will from the government, is needed. Keywords: revitalization, character education, learning of social studies